The EU model and Turkey: A case for thanksgiving? - Christina Hartler; Sam Laird (World Trade Organization (WTO), 1999)
The EU model is being progressively transmitted to other economies through expansion of membership and various preferential agreements. Since EU trade polices have been criticised in a number of respects, this could be a matter of concern to the international community. However, in the case of the customs union between the EU and Turkey, the result seems to have been generally beneficial to both partners as well as third countries. In areas such as agriculture, state aids, anti-dumping and TRIMS there is as yet no alignment but it would be hard to see that alignment would lead to any market opening in Turkey.
Keywords: F13; 330; Customs unions; trade policy; WTO